Vesicular Localization and Activity-Dependent Trafficking of Presynaptic Choline Transporters - Ferguson, Shawn M. (J Neurosci, 2003)
Presynaptic synthesis of acetylcholine (ACh) requires a steady supply of choline, acquired by a plasma membrane, hemicholinium-3-sensitive (HC-3) choline transporter (CHT). A significant fraction of synaptic choline is recovered from ACh hydrolyzed by acetylcholinesterase (AChE) after vesicular release. Although antecedent neuronal activity is known to dictate presynaptic CHT activity, the mechanisms supporting this regulation are unknown. We observe an exclusive localization of CHT to cholinergic neurons and demonstrate that the majority of CHTs reside on small vesicles within cholinergic presynaptic terminals in the rat and mouse brain. Furthermore, immunoisolation of presynaptic vesicles with multiple antibodies reveals that CHT-positive vesicles carry the vesicular acetylcholine transporter (VAChT) and synaptic vesicle markers such as synaptophysin and Rab3A and also contain acetylcholine. Depolarization of synaptosomes evokes a Ca(2+)-dependent botulinum neurotoxin C-sensitive increase in the V(max) for HC-3-sensitive choline uptake that is accompanied by an increase in the density of CHTs in the synaptic plasma membrane. Our study leads to the novel hypothesis that CHTs reside on a subpopulation of synaptic vesicles in cholinergic terminals that can transit to the plasma membrane in response to neuronal activity to couple levels of choline re-uptake to the rate of ACh release.